Standardization of an economical formulation for fish-balls - Libunao, Lariza G.; Sales, Alicia C. (1989.)
Fishballs were prepared using Labahita fish (Acanthurus bleekeri, Linn.). The best binder from among all-purpose flour, cornstarch and cassava starch for use in fishball making was determined through sensory evaluation of the fishballs for color, odor, flavor, texture and general acceptability. All-purpose flour was judged to be the best binder based on the general acceptability scores. The most acceptable level of usage of all-purpose flour was found to be 20% based on sensory evaluation and cost-analysis. Microbiological quality of the fishballs was monitored for a period of two weeks at three-day intervals. Two batches of fishballs were prepared, one was treated with potassium sorbate and the other was not. It was found that the addition of the preservative lowered the microbial load of the fishballs although both samples exhibited the acceptable microbiological limits even after two weeks of storage.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Fishery products